2013
DOI: 10.1007/s11357-013-9511-5
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated mesangial cell proliferation related to store-operated Ca2+ entry in aged rat: the role of STIM 1 and Orai 1

Abstract: Store-operated Ca 2+ entry (SOCE) is a common and ubiquitous mechanism regulating Ca 2+ influx into cells and participates in numerous biological processes including cell proliferation. Glomerular mesangial cells (GMCs) play a role in the regulation of the glomerular filtration rate. From a clinical point of view, many physiological functions alter with age. In the present study, we used angiotensin II, glucagon, and the sarco/endoplasmic reticulum membrane Ca 2+ pump inhibitor thapsigargin to deplete the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
2
14
1
Order By: Relevance
“…Target proteins in the thoracic aorta or mesenteric arteries were examined as previously described . Briefly, proteins were extracted with detergent extraction buffer containing 1% Triton X‐100, 150 mM NaCl, 50 mM Tris‐HCl, 1% sodium deoxycholate, 0.1% SDS, pH 8.0, plus protease inhibitor cocktail tablets and were separated on a 10% SDS‐polyacrylamide gel.…”
Section: Methodsmentioning
confidence: 99%
“…Target proteins in the thoracic aorta or mesenteric arteries were examined as previously described . Briefly, proteins were extracted with detergent extraction buffer containing 1% Triton X‐100, 150 mM NaCl, 50 mM Tris‐HCl, 1% sodium deoxycholate, 0.1% SDS, pH 8.0, plus protease inhibitor cocktail tablets and were separated on a 10% SDS‐polyacrylamide gel.…”
Section: Methodsmentioning
confidence: 99%
“… 7 9 In advanced aging, the balance of Ca 2+ in cells is gradually lost, which may become a profound factor altering cellular physiological function. 10 12 …”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that changed SOCE in kidney mesangial cells with aging affected cell proliferation. 12 However, whether SOCE and related vasoconstriction is changed in VSMCs from different vascular beds with aging remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Since TRPC1 is a Ca 2ϩ -permeable channel expressed in kidney cells (10), the results of Niehof and Borlak's study suggest that HNF4␣ may affect diabetic renal changes by regulating renal cell Ca 2ϩ signaling. STIM1-gated Ca 2ϩ channels participate in the Ca 2ϩ response in glomerular MCs (39,42), and dysfunction of MCs contributes to the progression of diabetic kidney disease. Furthermore, the promoter region of Stim1 has a HNF4␣-binding consensus, which was identified by the F-MATCH program (http://www.gene-regulation.com/ cgi-bin/pub/programs/fmatch/ffa2.cgi).…”
mentioning
confidence: 99%